Cellular functions of LRRK2 implicate vesicular trafficking pathways in Parkinson's disease. (15th December 2016) - Cookson, Mark R.
Abstract : Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene, associated with Parkinson's disease, have been shown to affect intracellular trafficking pathways in a variety of cells and organisms. An emerging theme is that LRRK2 can bind to multiple membranous structures in cells, and several recent studies have suggested that the Rab family of small GTPases might be important in controlling the recruitment of LRRK2 to specific cellular compartments. Once localized to membranes, LRRK2 then influences downstream events, evidenced by changes in the autophagy–lysosome pathway. Here, I will discuss available evidence that supports or challenges this outline, with a specific emphasis on those aspects of LRRK2 function that have been controversial or remain to be fully clarified.